Case Report: Intercurrent infections in COVID-19-induced sustained immunodepression: is interferon gamma a suitable drug? - De Waard, Aurianne; Lefebvre, Laurent; Textoris, Julien; Payen, Didier (Frontiers in Immunology, 2023)
Acute immuno-depression syndrome (AIDs) had been observed in many life-threatening conditions leading to the Intensive Care Unit. and is associated with recurrent secondary infections. We report one COVID-19 patient with a severe ARDS, demonstrating acute immunodepression syndrome lasting for several weeks. The occurrence of secondary infections despite long treatment by antibiotics led to combined interferon γ (IFNγ) as reported previously. The response to IFNγ was evaluated by the flowcytometry HLA-DR expression on circulating monocytes, which was repeated from time to time. The severe COVID-19 patients responded well to IFNγ without adverse events.